REDSAIN LOGO USAHA ROTI DAN KUE ANITA PAYAKUMBUH - FAUZAN AGUNG, Dra. Zubaidah, M.Sn., Riri Trinanda, S.Pd., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Bread and Cake Anita is one of cooky company in Payakumbuh. It is located at Kemuning Street number 9 at Koto Tangah, Payakumbuh. It was pionered by Anita Saura since 2007 by selling “ragam” cake and “bolu batik”. The target consuments of is company is especially for children at the age of 6-12 years old. This company has it’s own production place and distribution unit which distribute it’s products not only in Payakumbuh, but also to others regions like Duri and Pekanbaru.Actually, Bread and Cake Anita has logo but it did not have strong visual identity. It was caused by the logo didn’t use the principle and elements of design well. For examples, simplicity principle which can make the logo become simple and easy to remember, unity principle to get harmony impression in the logo when there was the form element that didn’t have relationship with this company that made the identity of Bread and Cake Anita Company become weak.Redesign of logo consist of collecting of the data, analize the data and redesign the new logo. Trough SWOT, data about Bread and Cake Anita and target consuments was analized to get a concept of redesign logo. In the process redesigning the new logo, the concept of redesigning was implemented creatively in visualized logo. As the result, a new logo of Bred and Cake Anita which consist of image of that company and actualized in the identity system of the company including stationery, supporting media like poster, x-banner, neon box, t-shirt, cup, sticker, secondary cover, so the new image of Bread and Cake Anita could be recognize by society.Key words: Logo, Redesign, Identity.